Masdevallia purocafeana, a new species of Orchidaceae from Cordillera del Toisán, northwestern Ecuador - Monteros, Marco F.; Mogrovejo, Adriana L.; Iturralde, Gabriel A.; Baquero, Luis E. (Phytotaxa, 2022)
A new species of Masdevallia genus is described here. Masdevallia purocafeana is immediately recognized by having conspicuously broad, echinate, and strongly reflexed lateral sepals. It is compared to Masdevallia alexandri but differs by having an oblong, shallowly concave, yellow-green dorsal sepal variegated with purple towards the apex, oblong petals light pink suffused with yellow and spotted with purple, and ovoid-ovate, reflexed light pink lip, dotted with pale light red.